Mapping the Tonotopic Organization in Human Auditory Cortex with Minimally Salient Acoustic Stimulation - Langers, Dave R.M. (Oxford University Press, 2012)
Despite numerous neuroimaging studies, the tonotopic organization in human auditory cortex is not yet unambiguously established. In this functional magnetic resonance imaging study, 20 subjects were presented with low-level task-irrelevant tones to avoid spread of cortical activation. Data-driven analyses were employed to obtain robust tonotopic maps. Two high-frequency endpoints were situated on the caudal and rostral banks of medial Heschl's gyrus, while low-frequency activation peaked on its lateral crest. Based on cortical parcellations, these 2 tonotopic progressions coincide with the primary auditory field (A1) in lateral koniocortex (Kl) and the rostral field (R) in medial koniocortex (Km), which together constitute a core region. Another gradient was found on the planum temporale. Our results show the bilateral existence of 3 tonotopic gradients in angulated orientations, which contrasts with colinear configurations that were suggested before. We argue that our results corroborate and elucidate the apparently contradictory findings in literature.